The Metaphorical Meanings of Animals and Cultural and Social Reflections of Tak-Bai (Je-Hay) Proverbial Idioms - Uppakandee, Yutthichai; Yuttapongtada, Methawee (Parichart Journal, 2024)
This article aims to study the metaphorical meanings of animals including metaphorical meaning procedures in Tak-Bai (Je-Hay) proverbial idioms, and investigate cultural and social reflections on animals in Tak-Bai (Je-Hay) proverbial idioms. The data were collected from Tak-Bai with Malay Proverbial Idioms, the book from the Southern Thai Tak-Bai Dialect Conservation project by Narathiwat Provincial Cultural Office. There are 45 proverbs and idioms relating to animals that are categorized using componential analysis. The results reveal seven types of metaphorical meanings consisting of metaphorical meaning of humans, metaphorical meaning of qualifications, metaphorical meanings of actions, metaphorical meanings of symptoms, metaphorical meanings of habits, metaphorical meaning of dangers, and other types of metaphorical meanings. With regards to animal categorizations, 18 groups of animals used in Tak-Bai proverbs were birds, cows, chickens, ants, dogs, cats, deer, fish, snakes, monitor lizards, chameleons, tigers, turtles, lizards, hornets, crocodiles, buffalo, and lice. The animal mostly used in proverbs is chicken. For cultural and social reflections on animals in Tak-Bai (Je-Hay) proverbial idioms, five aspects were found: geography, occupation, sports, traditional games, animal raising, and values. In addition, some animal terms were not used in Thai central proverbs. Instead, some appeared in Tak-Bai proverbs and idioms, for example, rattlesnake, cuckoo egg, and Lan (monitor lizard). It significantly shows the difference between central and Tak-Bai proverbs and idioms. Also, it reflects the uniqueness of such local proverbs.